PENGARUH PERMAINAN TRADISIONAL BOI-BOIAN TERHADAP KARAKTER PERCAYADIRI SISWA USIA 10 "“ 12 TAHUN SD SALOMO PONTIANAK - Lusiana Manik, Dwi; Yunitaningrum, Wiwik; Fachrurrozi Bafadal, Muhammad; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The problem in this study is the lack of self-confidence of students in learning. This study aims to determine the effect of the traditional boi-boian game on the character of self-confidence. The method used in this study is a pre-experimental method with the form of one group pretest and posttest research. This research uses total sampling, the population with a sample of all students following the criteria of specific age indicators with a sample of 38 and a population of 38 students using a pretest at the beginning and a posttest at the end of the study. The data analysis technique was a t-test with the help of SPPS version 22. The results showed an effect of the traditional boi-boian game on increasing self-confidence. The t-test result was sig. (2-tailed) for confidence 0.000 0, 05, then the results of the posttest group obtained the average self-confidence of the pretest group, which is 60.68. It can be concluded that the traditional boi-boian game influences the self-confidence of students at Solomon Elementary School, Pontianak City.